Prelude to prison: student perspectives on school suspension - Weissman, Marsha (Syracuse studies on peace and conflict resolution, 2015)
Chapter 1. Introduction: learning from Jayda -- Chapter 2. The American gulag: entwining schools into the carceral state -- Chapter 3. Alternative schools and zero tolerance: from liberation learning to social control -- Chapter 4. Engagement in the question: reflections on setting and method -- Chapter 5. Backstories: the lives of marginalized kids -- Chapter 6. "Bad decisions": the suspension incidents -- Chapter 7. "They never want to listen to us": the process of being suspended -- Chapter 8. "It's so non-regular": going to alternative school -- Chapter 9. "We have a Mike Tyson here": labels, rejection, and stigma -- Chapter 10. "At least somebody wanted to see me do good": what kids think makes a difference -- Chapter 11. Schools, social reproduction, and the making of prisoners: theory and literature -- Chapter 12. Conclusion: "we all activists now